ANALISIS DAMPAK SERVICE PERFORMANCE DAN KEPUASAN TERHADAP LOYALITAS PELANGGAN - - Mulyana; - Sufiyanor (Majalah Ilmiah Sultan Agung, 2009)
Transportation safety now becomes governmental focus because frequently happened transportation accident, one of them is sea transportation. That condition make sea transportation company must improve their service performance to give excellent service to their customer, so that customer becomes satisfying and loyal.Problem formulation at this research is about how service performance influence customer loyalty and whether consumer satisfaction moderating the relation of between both the variables. Population at this research is all passenger of PT. Dharma Lautan Utama (DLU) Semarang in 2008 that leaving from Tanjung Emas Harbour, Semarang. Sampling method is purposive convenient sampling. Data analytical method in this research used linear regression analysis.Linear regression result between service performance to customer loyalty indicates that regression coefficient of service performance variable (X1) is 0.997 with positive value and significant, its proven by significant value < 0,05. This result means that service performance influences customer loyalty with positive direction. So, excelsior service performance from employee will make customer loyalty. Absolute difference value test result indicates that variable coefficient of consumer satisfaction(X!) has positive value and significant, this result proves that consumer satisfaction is moderating variable in relation between service performance and customer loyalty. The result indicates that positive influence from service performance to customer loyalty would very height when consumer satisfaction is also height. Keyword: service performance, consumer satisfaction, and customer loyalty